Progressive Facial Ulcer: A Case Report of Pyoderma gangrenosum - Zhang XQ; Tang ZW; Jing J (Dove Medical Press, 2024)
Xian-Qi Zhang,* Zhen-Wei Tang,* Jing Jing Department of Dermatology, Second Affiliated Hospital, Zhejiang University School of Medicine, Hangzhou, 310009, People's Republic of China*These authors contributed equally to this workCorrespondence: Jing Jing, Department of Dermatology, Second Affiliated Hospital, Zhejiang University School of Medicine, Hangzhou, 310009, People's Republic of China, Tel +86 571 87784558, Fax +86 571 87783504, Email haitong1987@163.comAbstract: Pyoderma gangrenosum (PG) is a rare neutrophilic dermatosis characterized by rapidly developing and painful skin ulcers with distinctive features. As far as we are concerned, there is no previous case report on facial PG in East-Asia. In this case, we describe a case of a 79-year-old man with a 3-month history of progressive painful ulcers on his cheek and upper lip. Initial suspicion of atypical mycobacterium infection led to an ineffective treatment regimen. Comprehensive infectious testing yielded negative results, and a positive pathergy test indicated a potential diagnosis of PG. A skin biopsy confirmed the diagnosis, and the patient showed significant improvement with intravenous methylprednisolone and oral cyclosporine treatment. After three months, complete resolution of the lesions was achieved without recurrence. The case highlights the diagnostic challenges associated with PG, which is often misdiagnosed due to its resemblance to other conditions. Thorough evaluation is crucial to exclude alternative diagnoses, particularly cutaneous infections. Clinical morphology, tissue biopsy, and culture are essential for accurate diagnosis. The presence of pathergy, the development of new lesions following minor trauma, can also be a diagnostic clue.Keywords: Pyoderma gangrenosum, neutrophilic dermatosis, ulcer